Business Model Analysis in the Development of Yasaka Chicken Culinary Business Branches in Bandar Lampung - Nindi Sali Agusta; M. Oktavianur; Niki Agus Santoso (The Eastasouth Journal of Social Science and Humanities, 2026)
This study aims to analyze the implementation of the Business Model Canvas (BMC) in supporting the expansion of Yasaka Chicken culinary business branches in Bandar Lampung. The research employed a qualitative case study approach using primary data collected through in-depth interviews with business owners, operational managers, employees, suppliers, and loyal customers, complemented by secondary data from company documents and relevant literature. The analysis was conducted using the nine components of the Business Model Canvas, namely Customer Segments, Value Proposition, Channels, Customer Relationships, Revenue Streams, Key Resources, Key Activities, Key Partnerships, and Cost Structure. The findings reveal that the successful expansion of Yasaka Chicken branches is strongly influenced by a clear understanding of customer segments, a distinctive value proposition, effective utilization of digital and physical channels, and the implementation of standardized operational procedures across outlets. Strategic partnerships with suppliers and online delivery platforms also contribute significantly to operational efficiency and business scalability. In addition, the identification of revenue streams and cost structures provides valuable support for financial planning and profitability management during expansion. This study demonstrates that the Business Model Canvas serves not only as an analytical framework for evaluating business performance but also as a strategic tool for supporting managerial decision-making and sustainable branch development. The findings contribute to the literature on business model implementation in culinary enterprises and provide practical recommendations for businesses seeking growth in competitive urban markets.